Controller design and experimental validation of a very low frequency high-voltage test system. (April 2015) - Kemmetmüller, W.; Eberharter, S.; Kugi, A.
Abstract: This paper presents the design of a quasi optimal controller for a new type of very low frequency (VLF) high-voltage test system for on-site cable tests. The test system is based on the differential resonance technology (DRT), which allows a light weight and compact construction. The high requirements regarding quality and accuracy of VLF test voltages can only be achieved with a suitable control concept. In this work, a two degrees-of-freedom control strategy comprising a feedforward and a feedback control in combination with an estimator for the unknown cable capacitance is proposed. The controller design is based on an envelope model which describes the (nonlinear) envelope dynamics of the occurring amplitude modulated signals. The feasibility of the proposed control strategy is verified by a number of measurements on a prototype system for cable tests up to 200 kV rms. The measurement results show that the generated test voltage has a total harmonic distortion (THD) of less than 0.1%, which is significantly better than the requirements of sinusoidal VLF test voltages. Moreover, the control strategy has the ability to cover a wide range of cable capacitances, desired amplitudes of the output voltage and desired test frequencies.